Gender gaps in land rights: Explaining different measures and why households differ in Myanmar - Lambrecht, Isabel B.; Mahrt, Kristi; Synt, Nang Lun Kham; Ei Win, Hnin; Win, Khin Zin (Wiley, 2023)
Measuring and understanding gender differences in property rights is key to informing policy decisions and guiding investments aimed at fostering gender equality. However, there are a myriad ways of assessing property rights. Firstly, we assess which indicators to use and why it matters, focusing on rural Myanmar. Myanmar provides an interesting setting, as a large part of the population customarily follows joint property rights in marriage and upon dissolution of marriage and inheritance. However, documented property rights are in the household head's name – usually a male household member. We find that capturing de facto transfer rights is essential, but understanding discrepancies between reported transfer rights and documented rights will be key to policymakers. Capturing agricultural decision-making should remain a priority for agricultural projects. Second, we perform household- and intra-household level analyses to explore why we find joint land rights in some, but not all, households; and why some household members have less land rights than others. A common property rights regime positively reinforces women's land rights, but incompletely so. Within households, a person's role in the household, age, and key life cycle events such as parenthood and marriage are key determinants of having land rights.